1994
DOI: 10.1002/ange.19941061542
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesestudien an Pyridazomycin

Abstract: Über einen unerwarteten Aminosäuremetabolismus produziert eine Subspezies des Bodenbakteriums Streptomyces violaceoniger das fungizide Antibioticum Pyridazomycin 1‐Cl. So ergaben Fütterungsversuche mit isotopenmarkierten Vorstufen, daß 1 aus Ornithin, Glycin und wahrscheinlich Oxalacetat aufgebaut wird.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Biosynthetic investigations of the azoxy‐containing antibiotic valanimycin ( 1 )2 and the antifungal antibiotic pyridazomycin ( 2 )3a (Figure 1) have shown that both of these natural products are derived from the condensation of amino acids. Pyridazomycin3b was the only natural product known to contain a pyridazine ring until the phthalazinone meroterpenoid azamerone ( 3 ) was isolated from the marine sediment‐derived bacterium Streptomyces sp.…”
Section: Methodsmentioning
confidence: 99%
“…Biosynthetic investigations of the azoxy‐containing antibiotic valanimycin ( 1 )2 and the antifungal antibiotic pyridazomycin ( 2 )3a (Figure 1) have shown that both of these natural products are derived from the condensation of amino acids. Pyridazomycin3b was the only natural product known to contain a pyridazine ring until the phthalazinone meroterpenoid azamerone ( 3 ) was isolated from the marine sediment‐derived bacterium Streptomyces sp.…”
Section: Methodsmentioning
confidence: 99%
“…griseofuscus , inhibited the growth of Mucor hiemalis [ 95 ]. Pyridazomycin ( 86 ) and its analog ( 87 ), as chloride salts showed antimicrobial activity [ 96 ]. Compounds ( 88 or 89 ), also known as 8-azaguanine, is produced from guanine by Spteptomyces albus [ 97 ].…”
Section: Azo Metabolites Derived From Actinomycetes and Fungal Speciementioning
confidence: 99%
“…166 The biosynthesis of pyridazomycin (175) has also been studied. 167 Pyridazocidin (176) was isolated almost a decade after the discovery of 175 from a strain of Streptomyces sp., collected from loam soil in Honduras. 168 Pyridazocidin exhibits significant phytotoxicity, which operates via reversible redox reaction linked to photosynthetic electron transport, a highly unique mode of action among natural products.…”
Section: Journal Of Natural Productsmentioning
confidence: 99%
“…Studies showed that 175 exhibits significant antifungal activity, along with minor inhibitory effects against B. subtilis . The biosynthesis of pyridazomycin ( 175 ) has also been studied . Pyridazocidin ( 176 ) was isolated almost a decade after the discovery of 175 from a strain of Streptomyces sp., collected from loam soil in Honduras .…”
Section: Natural Products Containing An N–n Bondmentioning
confidence: 99%